Web-Based Sales Information System Model for Residential Kaveling Land - Romiyadi, Rizar; Ahriza, Muhammad; Fitriyadi, Fitriyadi; Ariannor, Wahyudi (STMIK Banjarbaru, 2025)
Companies engaged in kaveling land sales still rely on manual methods in their sales processes. Manual methods, such as record-keeping and direct communication without an integrated system, are considered less relevant as they pose risks of information delays, data inaccuracies, and lack of transparency. This study aims to develop a web-based information system to accelerate reservations, simplify data management, and enhance sales transparency. The system was developed using a prototyping approach and tested through blackbox testing. The results indicate that the system has successfully become an effective solution for improving the efficiency of sales transaction management. The developed system enables prospective buyers to reserve plots more quickly, easily, and transparently. This system can support the effectiveness of the sales process. Further development is recommended by adding online transaction features and integrating an interactive map.Keywords: Information system; Land plot sales; Installment payment; Prototyping; Blackbox testing AbstrakPerusahaan yang bergerak di bidang penjualan tanah kavling masih menggunakan metode manual dalam proses penjualan. Metode manual seperti pencatatan dan komunikasi langsung tanpa sistem terintegrasi dinilai kurang relevan karena berisiko menyebabkan keterlambatan informasi, ketidakakuratan data dan kurangnya transparansi. Penelitian ini bertujuan membangun sistem informasi berbasis web untuk mempercepat pemesanan, mempermudah pengelolaan data dan meningkatkan transparansi penjualan. Sistem dikembangkan menggunakan pendekatan prototyping dan diuji dengan Blackbox testing. Hasil penelitian menunjukkan bahwa sistem berhasil menjadi solusi efektif dalam meningkatkan efisiensi pengelolaan transaksi penjualan. Sistem yang dikembangkan memungkinkan calon pembeli untuk melakukan pemesanan kavling secara lebih cepat, mudah dan transparan. Sistem ini dapat mendukung efektivitas penjualan. Pengembangan lebih lanjut disarankan dengan menambahkan fitur transaksi daring dan integrasi peta interaktif.